Aspects of Individual and Categorical Differences In Relation to Their Gender, Subject and Locality: - (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Education is conceived as a powerful agency, which isinstrumental in bringing about the desired changes in the social and culturallife of nation. The whole process of education is shaped and moulded by thehuman personality called the teacher who plays a pivotal role in any system ofeducation.